PENGUASAAN PENYUSUNAN MODUL AJAR GURU PPKn DI SMP NEGERI 3 GALESONG SELATAN KABUPATEN TAKALAR - Bachtiar, Nuraeni; Haris, Hasnawi; Mustari, Mustari (Jurnal Tomalebbi, 2025)
Abstract: This study aims to find out, (1) the ability of PPKn teachers at SMP Negeri 3 South Galesong in compiling teaching modules in accordance with the Independent Curriculum, (2) the obstacles faced by PPKn teachers at SMP Negeri 3 Galesong Selatan in compiling teaching modules in accordance with the Independent Curriculum, (3) the efforts made by PPKn teachers at SMP Negeri 3 South Galesong in compiling teaching modules in accordance with the Independent Curriculum. This study uses a qualitative method with a descriptive approach, while the data collection procedures used are interviews, observations, and documentation. The results of the study show that (1) Teachers have the ability to compile teaching modules based on the Independent Curriculum at a "moderate" level. The main components in the teaching module have been well arranged, but there is still room for improvement, especially in integrating the values of the Pancasila Student Profile and the implementation of project-based learning. (2) Teachers face obstacles such as limited resources, lack of advanced training, and administrative workloads that reduce the time to prepare teaching modules optimally. (3) Efforts have been made by teachers to improve the quality of teaching modules, including through participation in the Subject Teacher Conference (MGMP), the use of digital technology, and independent training. Teachers also use local contexts to make learning materials more relevant and easy for students to understand. However, the implementation of project-based learning methods has not been fully implemented due to limited technical understanding.